Workload Analysis System Optimization through the Integration of an Interactive Dashboard - Karisa, Tiara; S, Ahmad (PT. Lentera Ilmu Publisher, 2025)
In the era of digital transformation and bureaucratic reform, optimizing organizational performance in police institutions demands effective workload management. Workload analysis (Analisis Beban Kerja/ABK) is essential for ensuring fair task distribution that aligns with personnel capacity and competence. The Community Development Unit (Binmas) of the South Sumatra Regional Police plays a pivotal role in building public trust and cooperation. However, the absence of an integrated system to analyze workload distribution has resulted in potential inefficiencies, imbalanced task assignments, and increased work stress. Recent findings highlight a significant link between workload and stress levels among police personnel, emphasizing the urgency of system optimization. This study proposes the integration of an interactive dashboard to enhance the effectiveness of workload analysis in the Binmas Unit. Drawing on successful implementations such as the e-dikbangspes system and SI-ABK Precision application, the research underscores how dashboard technology can streamline data access, improve staffing decisions, and support the development of a more responsive organizational structure. By focusing on the Binmas Unit, this study aims to close the existing technological gap and contribute to improved personnel management and institutional performance through digital innovation in workload monitoring.